Surgery in mycetoma-endemic villages: unique experience. (30th January 2021) - Mohamed, El Samani Wadaa; Bakhiet, Sahar Mubarak; El Nour, Mustafa; Suliman, Suliman Hussein; El Amin, Hajo Mohamed; Fahal, Ahmed Hassan
Abstract: In this communication, the Mycetoma Research Center (MRC), University of Khartoum, WHO Collaborating Center on Mycetoma, shares its experience in field surgery for mycetoma. The surgery was conducted in two mycetoma-endemic villages in Sennar and the White Nile States in collaboration with local health authorities, local community leaders, activists and civil society associations. In these villages, the local health centres were renovated and operating theatres were established. The medical and health missions' team was established at the MRC. The team conducted 15 missions over the period 2013–2020 and 1200 mycetoma patients received surgical treatment. These included wide local excisions, minor amputations and debridement that were conducted under spinal or ketamine analgesia. The missions adopted a community holistic management approach, which included medical and surgical treatment, health education sessions, village hygiene improvement and socio-economic support. The latter offered the mycetoma amputees artificial prosthesis and financial support. All these services were provided free of charge. This holistic approach proved to be effective for early case detection and management, optimal treatment outcome and favourable disease prognosis. During the study period, the number of patients with massive lesions and the amputation rate decreased and this reduced the medical and socio-economic disease burdens on patients and families. This treatment approach needs the collaboration of all stakeholders for sustainability and quality improvement.